2021
DOI: 10.3390/ijerph182312496
|View full text |Cite
|
Sign up to set email alerts
|

Does Childcare Work Promote Cardiorespiratory Fitness and Health? A Cross-Sectional Study of Danish Childcare Workers Based on Accelerometry and Heart Rate Measurements

Abstract: Childcare workers are reported to have poor cardiorespiratory fitness and health. The Goldilocks Work Principle argues that productive work should be designed with the right composition, intensity and alternations of physical behaviors so that workers get fit and healthy. The purpose of this study was to investigate: (1) composition, (2) intensity and (3) alternations of physical behaviors during work and leisure among childcare workers. Data were collected using accelerometers and heart rate monitors over fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The software OMGUI was used to initiate accelerometers and download accelerometer data. Workdays were considered valid if they contained ≥4 hours of accelerometer measurements ( 7 , 21 ). We did not collect heart rate or accelerometer measurements on childcare workers that (i) were allergic to adhesive tape, (ii) had fever on the test day or (iii) were pregnant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The software OMGUI was used to initiate accelerometers and download accelerometer data. Workdays were considered valid if they contained ≥4 hours of accelerometer measurements ( 7 , 21 ). We did not collect heart rate or accelerometer measurements on childcare workers that (i) were allergic to adhesive tape, (ii) had fever on the test day or (iii) were pregnant.…”
Section: Methodsmentioning
confidence: 99%
“…It is well documented that high-intensity physical activity can improve cardiorespiratory fitness and health ( 6 ). Thus, the low cardiorespiratory fitness and health among a high proportion of childcare workers could be a result of their physical activity being of insufficient intensity to increase cardiorespiratory fitness ( 7 ). Accordingly, we have found that childcare workers have only about 2.5 min of high-intensity occupational physical activity per day [≥60% of heart rate reserve (HRR)] ( 7 ).…”
mentioning
confidence: 99%
See 1 more Smart Citation